Analysis of the Success of Early Breastfeeding Initiation on Stunting in Infants Aged Less Than 12 Months - Agustini, Fenty; Apriasih, Hapi; Lestari, Ayuning Tias Budi; Rahayu, Novita Tri (Genius Journal, 2024)
Introduction: The incidence of stunting in Tasikmalaya Regency has decreased from 41.7% to 24.4%, but in 2022 there will be an increase of 2.7 points to 27.2%. The Tasikmalaya Regency Government has designated 67 villages as special locations for stunting intervention convergence in 2023. Cikunir Village, Singaparna District, Tasikmalaya Regency is one of the villages with a stunting prevalence that exceeds the set limit of 20%. Objective: The aim of this research is to determine the success of implementing of early breastfeeding initiation in Cikunir Village, Singaparna District, Tasikmalaya Regency on 2024. Method: This research method is qualitative with the aim of knowing the implementation of early breastfeeding initiation, mother's knowledge about early breastfeeding initiation, family motivation and the implementation of early breastfeeding initiation in stunted babies less than 12 months. Result: Based on the results of interviews during the implementation of early breastfeeding initiation, it is known that not a single baby succeeded in finding and sucking its mother's nipple, most did not exclusively breastfeed their babies, most did not know about early breastfeeding initiation, some most do not get motivation from their husbands and families in implementing early breastfeeding initiation and most do not prepare themselves for breastfeeding such as not taking care of their breasts during pregnancy. Conclusion: This research is expected to increase mothers' knowledge and motivation in carrying out early breastfeeding initiation.